Experimental investigation on drag and heat flux reduction in supersonic/hypersonic flows: A survey. (December 2016) - Wang, Zhen-guo; Sun, Xi-wan; Huang, Wei; Li, Shi-bin; Yan, Li
Abstract: The drag and heat reduction problem of hypersonic vehicles has always attracted the attention worldwide, and the experimental test approach is the basis of theoretical analysis and numerical simulation. In the current study, research progress of experimental investigations on drag and heat reduction are summarized by several kinds of mechanism, namely the forward-facing cavity, the opposing jet, the aerospike, the energy deposition and their combinational configurations, and the combinational configurations include the combinational opposing jet and forward-facing cavity concept and the combinational opposing jet and aerospike concept. The geometric models and flow conditions are emphasized, especially for the basic principle for the drag and heat flux reduction of each device. The measurement results of aerodynamic and aerothermodynamic are compared and analyzed as well, which can be a reference for assessing the accuracy of numerical results. Highlights: Experimental studies on drag and heat reduction for space mission vehicles were summarized. Quantitative measurements, as well as refined flow structures, are crucial for CFD results. Properties at high angle of attack are worth investigating, as well as their optimizations. The ways in actual engineering implementation for these schemes need further investigation.